Detection of a Novel Mutation on the Gene ESCO2 in a Pediatric Patient with Syndactyly - Ngoc, Nguyen Thy; Van Anh, Le Thi; Duong, Nguyen Thuy; Hai, Nong Van (VNU Journal of Science: Natural Sciences and Technology, 2020)
Syndactyly is a congenital disease caused by the limb formation abnormalities during fetal development. In this research, we studied the genetic mutations in a pediatric patient with 3 rd   and 4 th fingers were fused together, symmetrically using the whole exome sequencing techniques based on Next generation sequencing. The obtained data revealed a novel mutation located in exon 11 of the gene ESCO2 : c.1745A>G: p.582K>R. Sequence verification by Sanger sequencing confirmed the existence of this mutation in the patient as heterozygous form. In silico prediction using PredictSNP, PhD-SNP, PROVEAN or Polyphen-2 tools indicated that the mutation was likely to affect the structure and function of Acetyltransferase? (encoded by ESCO2 gene). Further studies will be performed to analyze the effect of this mutations on the intracellular protein network associated with syndactyly.